Fenomena Minat Masyarakat Indonesia Pada Forex Online ; Bagaimana Sudut Pandang Syariah ? - Sauril Rahmadi Hutabarat; Maryam Batubara (ITB AAS INDONESIA Surakarta, 2023)
The development of technology has shifted the pattern of forex transactions from corporate to retail, currently the interest of the Indonesian people is quite high in forex investment, but on the other hand there are also many investors who have failed, this article aims to find out how high the risk of investing through online forex applications. The research method used is a descriptive qualitative method, by conducting a literature review of various articles searched through published and perished applications, Google Scholar, and Google, the result obtained is that forex transactions have a very high risk, the majority of investors, especially beginners, fail in this business, besides that from the sharia side, forex transactions are only allowed to be limited to spot transactions and forward agreements, While transactions made on online applications are not intended for such transactions, so what is transacted in online forex applications is most likely an illegitimate transaction, besides that the investor's purpose is only to take advantage of the difference in value, not for the purpose of foreign trade, forex transactions on this online application are more speculation based on possible possibilities so that these activities can be categorized as usury and gambling, The high interest of the public, including Muslims, in online forex transactions is due to the high possibility of profits that can be obtained, and the lack of risk accountability, this happens due to the lack of level of knowledge related to Islamic risks and financial literacy, especially in the field of forex.